The influence of traditional service quality and bank size on trust in e-banking - Wong, David; Loh, Hwee Kuen Claire; Yap, Kenneth; Bak, Randall (School of Marketing, Curtin Business School, 2009)
This paper examines the role of situational normality cues (online attributes of the e-banking website) and structural assurance cues (size and reputation of the bank, and quality of traditional service at the branch) in a consumer?s evaluation of the trustworthiness of e-banking and subsequent adoption behaviour. Data were collected from a survey and a usable sample of 202 was obtained. Hierarchical moderated regression analysis was used to test the model. Traditional service quality builds customer trust in the e-banking service. The size and reputation of the bank were found to provide structural assurance to the customer but not in the absence of traditional service quality. Website features that give customers confidence are significant situational normality cues.Bank managers have to realise that good service at the branch is an opportunity to promote e-banking. They cannot rely on the bank?s size and reputation to ?sell? e-banking. This is the first study that examines how traditional service quality and a bank?s size and reputation influence trust in e-banking.